PENGEMBANGAN DESAIN MOTIF DAN PRODUK SULAM KOTO GADANG UNTUK MENDUKUNG INDUSTRI KREATIF - Ranelis Ranelis; Rahmad Washinton; Kendall Malik (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
The Development of Motifs and Koto GadangEmbroidery Designto Support Creative Industries”, aims to opti-mize the potential of Koto Gadang embroidery as one of the superior products of the Koto Gadang community, so that it can become a quality product that has distinctive characteristic not owned by other regions. The method used isexperimental, the research procedure carry out is by exploration and design. Exploration aims to find ideas or concepts through data extraction and literature studies, observations and interviews. The data that has been collected is processed and analyzed qualitatively then presented verbally, which becomes the basis of conducting design experiments.The design is the embodiment of the ideas and concepts produced by exploration into the designs of clothing, household and souvenir.This Research result has five motifs that sets up on each product such as the SiriahGadang design, the PucuakRabuang design, the ItiakPulangPatang design, the BungaMawar and the ItiakLadoHijau design.The motifs applyrepeatedly that displays following product shape.